Common Sense in Early 18th-Century British Literature and Culture : Ethics, Aesthetics, and Politics, 1680-1750 - Henke, Christoph (Buchreihe der Anglia, 2014)
In a time of political, epistemic and aesthetic revolutions, early 18th-century Britain saw the emergence of a public discourse of 'common sense' which had a lasting influence on clichéd concepts of cultural identity. By retracing the compensatory impulses of common sense discourse and highlighting the role of literary texts in its formation and dissemination, this study challenges the received view of Augustan England as a mere Age of Reason.